MFe6 X4 system (M = Mg, Sc, Zr; X = Al, Si, P, Ga, Ge, in, Sn, Sb) as possible ‘gap’ magnets - Alena Vishina; Rebecca Clulow; Daniel Hedlund; Vitalii Shtender; Peter Svedlindh; Martin Sahlberg; Olle Eriksson; Heike C. Herper (Science and Technology of Advanced Materials, 2025)
LiFe6Ge4, with a theoretically predicted saturation magnetization of 1 T, a magnetocrystalline anisotropy energy of 1.78 MJ/m3 and a Curie temperature of 620 K was suggested to be a promising permanent magnet as an outcome of a data-mining search. Magnetic measurements of the synthesized sample are reported here. Unfortunately, experiments revealed a weak ferromagnetic behaviour with magnetization values much below that predicted by theory. This discrepancy is analyzed in detail, and is attributed to the trigonal crystal symmetry that was missed in the previous characterisation of the material. The correct crystal structure is R[Formula: see text] mH (space group 166) and it is found here to have an antiferromagnetic ground state, as opposed to a theoretically predicted ferromagnetic state of the previously reported monoclinic crystal structure. Theoretical calculations show that element substitution can stabilize a ferromagnetic state of the trigonal crystal structure, with high values of saturation magnetization and magnetocrystalline anisotropy. The best results are seen for the Al or Ga substitution for Ge of the LiFe6 X4 compound.